Psychosis as an Isolated Manifestation of COVID-19 in Non-Demented Patients with Parkinson's Disease: Clinical Cases and Literature Review - G. Lokominaitė; R. Kaladytė Lokominienė (Neurologijos seminarai)
Psychotic disorders in patients with Parkinson's disease are usually associated with poor cognitive performance, comorbidities, and changes in treatment regime. Despite the recognition of cognitive deficit as a major risk factor for psychosis in Parkinson's disease, psychotic events have been reported in patients without dementia. SARS-CoV-2 is now recognized as a harmful invader of the nervous system, and defining its consequences still requires multidirectional research. Patients with Parkinson's disease may develop psychosis during COVID-19 infection. According to our observation, psychotic disorder seems to be an isolated manifestation of SARS-CoV-2 infection in Parkinson's disease. In this article, we present two clinical cases of non-demented patients with Parkinson's disease who underwent full vaccination against SARS-CoV-2. The patients were on stable antiparkinsonian medication, had no previous psychiatric disturbances, and developed psychosis as a consequence of COVID-19 without any other clinical signs of infection; no recurrent psychotic disorders were registered during the one-year follow-up. The discussion on diagnostic difficulties and treatment options includes a review of the literature. We recommend to perform reverse transcription polymerase chain reaction (RT-PCR) swab testing for SARS-CoV-2 in patients with Parkinson's disease who develop acute psychosis.